Enhanced strain response and energy harvesting capabilities of electrostrictive polyurethane composites filled with conducting polyaniline. (18th January 2016) - Jaaoh, Darika; Putson, Chatchai; Muensit, Nantakan
Abstract: The aim of this work was to study electrostrictive behavior and vibration energy harvesting performance of conductive polyaniline (PANI)/polyurethane (PU) composites at low percolation threshold. Polyurethane composites with various PANI contents (0–2 wt%) were fabricated by solution casting. AFM, TGA and DSC techniques were used to investigate the topography, intermolecular interactions and dispersion effects in these composites. Moreover, dielectric and mechanical properties were determined to characterize electrostriction and energy conversion behaviors. The experimental results indicated that the PANI filler in PU matrix improved the electromechanical coupling, which is related to the interfacial charges between these phases. When an external electric field was applied to the electrodes, the generated current increased with the PANI content. Theoretical power analysis supported the experimental results, demonstrating that 2 wt% PANI in PU gave the maximum output power in a low electric field at 20 Hz mechanical frequency. Consequently, conductive PANI dispersed into electrostrictive PU can provide high power density and good efficiency of electromechanical conversion.